2014
DOI: 10.1038/ncomms6314
|View full text |Cite
|
Sign up to set email alerts
|

Active accumulation of very diluted biomolecules by nano-dispensing for easy detection below the femtomolar range

Abstract: Highly sensitive detection of biomolecules is of paramount interest in many fields including biomedicine, safety and eco-pollution. Conventional analyses use well-established techniques with detection limits B1 pM. Here we propose a pyro-concentrator able to accumulate biomolecules directly onto a conventional binding surface. The operation principle is relatively simple but very effective. Tiny droplets are drawn pyro-electro-dynamically and released onto a specific site, thus increasing the sensitivity. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 39 publications
0
40
0
Order By: Relevance
“…Thanks to the largest known magnitude of spontaneous polarization at room temperature (≈78 μC cm −2 ), LN has been demonstrated to be useful for a wide variety of applications with the key advantage of being electrode‐free, and thus opening the route to more versatile configurations. These include, for example, dielectrophoresis‐based patterning of fluids and particles, nozzle‐free nanodispensing, reshaping, and even biosensing …”
Section: List Of Polymer Solutions Used For Fabricating the Pyroelectmentioning
confidence: 99%
“…Thanks to the largest known magnitude of spontaneous polarization at room temperature (≈78 μC cm −2 ), LN has been demonstrated to be useful for a wide variety of applications with the key advantage of being electrode‐free, and thus opening the route to more versatile configurations. These include, for example, dielectrophoresis‐based patterning of fluids and particles, nozzle‐free nanodispensing, reshaping, and even biosensing …”
Section: List Of Polymer Solutions Used For Fabricating the Pyroelectmentioning
confidence: 99%
“…Recent advancements in automated diagnostic platforms based on polymerase chain reaction (PCR) and enzyme-linked immunosorbent assays (ELISA) have enabled the routine detection of trace levels of nucleic acid and protein biomarker. Additionally, parallel research efforts in sample pre-concentration techniques have shown further potential for enhancement of traditional assays [3]. While these techniques achieve impressive results, all rely heavily upon a complicated sequences of sample preparation and amplification processes that limits their effectiveness outside of well-equipped laboratory environments [4].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, triamine/SDS can make the drops uniformly spread on a superhydrophobic surface over a wide range of We , as low as 2 and as high as 614. The uniform round shape with uniform distribution for the solutes is beneficial for highly sensitive detection in bioarrays …”
mentioning
confidence: 99%